THE EXPERIMENTAL STUDY OF COMPLETE PLATE CAPACITORS FOR DETERMINING A DIELECTRICAL CONSTANTA OF A MATERIAL - - Kurniasari (Widya Mandala Surabaya Catholic University, 2018)
Experiments and theories are two parts that cannot be separated in studying Physics. Many theories are built on experimental data and many theories fall because they conflict with experimental data. In addition, the role of experiments can also be used to help understand a physics material obtained in class. With this regard, a development research has been carried out to determine the dielectric constant of a material through parallel plate capacitor experiments, and experimental instructions. The research was carried out through stages: literature study, tools testing, experiments: taking and analyzing data, developing practical instruction modules and testing modules to the students. The results showed that through practicum parallel plate capacitors, dielectric constant of a material can be obtained. From the results of the experiment, the value of the dielectric constant was (8.60 ± 0.01) x 10 -1 for air; (2.1 ± 0.2) for plastic; and (4.3 ± 0.2) for glass. Based on the results of testing the module practicum instructions for students of a Physics Education Study Program, it was obtained the fact that students stated that the practicum instruction module was already developed well and could assist in carrying out parallel plate capacitor practicum.